The perspectives of stakeholders of intellectual disability liaison nurses: a model of compassionate, person‐centred care. Issue 7 (11th February 2016) - Brown, Michael; Chouliara, Zoë; MacArthur, Juliet; McKechanie, Andrew; Mack, Siobhan; Hayes, Matt; Fletcher, Joan
Abstract : Aims and objectives: To investigate the experiences of patients with intellectual disabilities, family and paid carers regarding the role of liaison nurses and the delivery of compassionate, person‐centred care. From this to propose a model of person‐centred care embedded in these experiences. Background: People with intellectual disabilities have a high number of comorbidities, requiring multidisciplinary care, and are at high risk of morbidity and preventable mortality. Provision of compassionate, person‐centred care is essential to prevent complications and avoid death. Design: A qualitative design was adopted with Interpretative Phenomenological Analysis for data analysis. Methods: Semistructured interviews and focus groups were conducted. Data were analysed with a focus on compassionate, person‐centred care elements and components. Themes were modelled to develop a clinically meaningful model for practice. Results: Themes identified vulnerability, presence and the human interface; information balance; critical points and broken trust; roles and responsibilities; managing multiple transitions; 'flagging up' and communication. Conclusions: The findings provide the first 'anatomy' of compassionate, person‐centred care and provide a model for operationalising this approach in practice. The applicability of the model will have to be evaluated further with this and other vulnerable groups. Relevance to clinical practice: This is the first study to provide a definition of compassionate, person‐centred care and proposes a model to support its application into clinical practice for this and other vulnerable groups.